KESIAPAN ARMADA TRUK SIAP OPERASI TERHADAP JUMLAH UNIT BARANG - DEDDY NURDIN; BAHARI PRADANA (Institut Transportasi dan Logistik Trisakti, 2015)
PT. Dressage Logistics Indonesia is a company engaged in logistics, especially trucking. Allegedly there is a relationship between the use of Ready Truck Operations with Goods These Units Falkirk. The method of data analysis used a simple linear regression, correlation coefficient analysis, and hypothesis testing (correlation test). Results of analysis and discussion revealed that there is a relationship between the number of trucks ready for operation on the number of units of goods are shown with a simple regression line is: y = - 17705.3 + 65,15X, meaning that when the growing number of trucks ready for operation up 1 (one) units, the number of units of goods having a gain of 65.15 units of goods. The correlation coefficient r = 0.64 means that the relationship variable X (number of trucks ready for operation) and Y (number of units of goods) is strong and positive. Determinant coefficient test figures show 40.96%. Hypothesis test results tcount> t table (2.62> 0.81246), then Ho = rejected and Ha = acceptable, meaning terhadapat significant relationship between the number of trucks ready for operation and the number of units of goods.